MANAJEMEN PENDIDIKAN KARAKTER DALAM MENUMBUHKAN AKHLAK SISWA DI MTS MA’ARIF 20 KALIREJO LAMPUNG TENGAH : INDONESIA - Muhamad Asror; Muhammad Qomarudinul Huda; Idham Juanda; Basirun (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2024)
ABSTRACK This research discusses Character Education Management at MTs Ma'arif 20 Kalirejo, Central Lampung. The concept discussed is the pattern of character growth of students, which is supported by various elements such as madrasa activities, rules and content of Islamic education lessons at MTs Ma'arif 20 Kalirejo, Central Lampung. Apart from these supporting factors, there are several strategies to advance the concept of character education management, including example, learning, empowerment, acculturation, training, and assessment. Currently, character has a crucial role in human life, especially for the nation's next generation. Therefore, character education is very important in the school environment. However, achieving character values ​​must be implemented through effective management. Character education management is a planned effort to ensure that students know, care about, and internalize values ​​so that they can develop their unique character. This process involves planning, organizing, implementing, and monitoring.